Testing the causality and cointegration relationship between GDP and exports in Libya (Economic studies journal, 2020)
The study aimed to clarify the relationship between exports and GDP during the period (2018-1970). The model is estimated depending on two variables namely current GDP as a dependent variable and total exports as an independent variable using a set of standard and statistical tools such as co-integration, Granger causality, and ECM error correction model utilised from the Eviews 10. The research proved that there is a short and long term equilibrium relationship between exports and GDP in Libya during the study period. There is two-way causal relationship between exports, GDP, and export growth leads to GDP growth.